Dependency of foreign workers in Malaysian construction industry / Mohd Arif Marhani ... [et al.] - Marhani, Mohd Arif; Adnan, Hamimah; Baharuddin, Har Einur; Esa, Mohd Reza; Hassan, Ahmad Arzlee (Faculty of Architecture, Planning & Surveying & UiTM Press, 2012)
The Malaysian construction industry plays an important role in generating wealth to the country and development of social and economic infrastructures and buildings. Due to unpleasant working conditions and availability of cheap foreign workers, majority of the construction companies preferred to hire them. Thus, the numbers of foreign workers has increased. In addition, employment of foreign workers has affected the economic growth, health and social problems such as malaria and cholera and robberies. This paper intends to identify the dependency factors of Malaysian construction companies on foreign workers in construction industry, the problems and also the effects of employment of them. The opinions and views of related construction companies were obtained from the questionnaire surveys and structured interviews which have been identified to give a clearer picture of the current situation of dependency level of foreign workers in Malaysia. It was found that low wages, longer working hours, higher education level by the local, availability of foreign workers and 3D's (dirty, difficult and dangerous) environment of site contributes to the problems of the foreign workers. It is important for the government to tighten the hiring rules of foreign workers and strengthening the national security, implementing the Industrialised Building System (IBS) and fully utilized the Construction Labour Exchange Centre Berhad (CLAB) and also the Construction Academy of Malaysia (CAM).